Physicochemical properties of choline chloride-based natural deep eutectic solvents (NaDES) and their applicability for extracting oil palm flavonoids - Che Zain, Mohamad Shazeli; Yeoh, Jen Xen; Lee, Soo Yee; Shaari, Khozirah (MDPI AG, 2021)
Oil palm (Elaeis guineensis Jacq.) leaf (OPL) is abundantly generated from oil palm plantations as biomass that is rich in bioactive metabolites, primarily flavonoids. Six natural deep eutectic solvents (NaDES) were synthesized using a direct heating technique from different combinations of choline chloride with 1,2-propanediol (PD), 1,4-butanediol (BD), glycerol (GLY), glucose (GLU), maltose (MAL) and lactic acid (LA). The synthesized NaDES were subjected to physicochemical and biological evaluations comprising physical appearance, density, water activity, viscosity, polarity, thermal behaviors, spectroscopic analysis, cytotoxicity, radical scavenging activities and solubility tests. Compared to aqueous methanol, the synthesized NaDES, which appeared as a slightly to moderately viscous transparent liquid, showed favorable physicochemical properties as extraction solvents with a low cytotoxicity profile on cultured fibroblast cells. Further, the NaDES obtained from the choline chloride:lactic acid (LA) combination showed high free radical scavenging characteristics. Hydrogen bonding interactions were shown to play a significant role in the formation of the NaDES. Further, ultra-high-performance liquid chromatography ultraviolet/photodiode array (UHPLC-UV/PDA) analysis revealed that the NaDES from the choline chloride:glycerol (GLY) combination had comparable efficiencies with aqueous methanol regarding extracting flavonoids (luteolin and apigenin derivatives) from OPLs. The results of the present study suggested that the tailor-made NaDES were not only easy-to-use, stable and safe solvents but also suitable for extracting bioactive phytochemical compounds. The study highlighted their potential as an alternative green technology for applications in oil palm biomass utilization programs.